Systematic Literature Review Method to Identify the Role of Momentum Flux on Atmospheric and Ocean Dynamics - Wahyuni, Siltia; Sulistiyono, Andi (Journal of Climate Change Society, 2024)
Atmospheric and oceanic momentum fluxes are important components in understanding the dynamic interactions between the atmospheric and ocean systems. Ocean momentum fluxes serve as the primary driver of ocean circulation, influencing current patterns and surface temperature distributions. Meanwhile, momentum transfer from the atmosphere to the ocean, influenced by factors such as wind speed and surface conditions, plays a major role in the formation of extreme weather and regional climate patterns. Therefore, it is important to understand the interaction mechanism of atmospheric and oceanic momentum fluxes on the impact of seasonal variability and its implication for climate change. This study aims to identify the role of momentum fluxes on atmospheric and ocean dynamics obtained from international journals during 2020-2024. There are 200 studies related to the role of momentum flux on atmospheric and ocean dynamics. The method used in this research is the Systematic Literature Review (SLR) method. The SLR method is used to identify, review, evaluate and interpret all available research with the topic area of the phenomenon of interest, with specific relevant research questions. The results explain that momentum fluxes play a role in global ocean circulation, wave formation and turbulence, interaction of momentum fluxes with the urban canopy layer, interaction of momentum fluxes with the surface layer, interaction of momentum fluxes with the surface layer and the deep ocean layer, and influence the dispersion of pollutants in urban areas